Pengaruh Pemberian Tugas Mandiri terhadap Hasil Belajar Mahasiswa pada Mata Kuliah Histologi - Serena, Nelda Anasthasia; Masitah, Masitah; Kurniawati, Zenia Lutfi (Biocaster : Jurnal Kajian Biologi, 2025)
This study aims to determine the effect of giving independent assignments on student learning outcomes in the Histology course. The method used was a quasi-experimental design with a pretest-posttest control group design. The study subjects consisted of two classes: a treatment class given independent assignments and a control class without similar treatment. Data were collected through pretests and posttests, then analyzed using paired t-tests and homogeneity of variance tests. The results showed a significant difference between pretest and posttest scores in the treatment class (p = 0.000 < 0.05), while the control class showed no significant difference (p = 0.348 > 0.05). These findings indicate that giving independent assignments can significantly improve student learning outcomes. Thus, independent assignments are effectively implemented as a learning strategy in the Histology course to train students' independence, responsibility, and critical thinking skills.